State Alcohol Policies, Binge Drinking Prevalence, Socioeconomic Environments and Alcohol's Harms to Others: A Mediation Analysis. (13th August 2020) - Cook, Won Kim; Li, Libo; Greenfield, Thomas K; Patterson, Deidre; Naimi, Timothy; Xuan, Ziming; Karriker-Jaffe, Katherine J
Abstract: Aims: Alcohol policy effects on alcohol's harms due to others' drinking (AHTO) and contextual factors that may mediate such policy effects have been understudied. This study examines state binge drinking prevalence as a mediator of the relationship between state alcohol policy and socioeconomic environments and individual-level AHTO. Methods: A nationally representative sample of US adults ( N  = 32, 401; 13, 873 males, 18, 528 females) from the 2000, 2005, 2010 and 2015 National Alcohol Surveys and the 2015 National Alcohol's Harm to Others Survey, administered in telephone interviews and based on random digit dialed sampling, were linked with state-level Alcohol Policy Scale (APS) scores, binge drinking prevalence and socioeconomic status (SES) data. Three 12-month AHTO measures were family/marriage difficulties, assault or vandalism and riding with drunk driver or having traffic accident. Three-level mediation analyses were conducted, controlling for gender, race, education, marital status, family problem-drinking history and state policing rate. Results: The effects of the APS on reduced risks for assault/vandalism and drinking-driving harms were significantly mediated by reduced state binge drinking prevalence. The APS had no direct or indirect effect on family/marital trouble. State SES had significant indirect effects on increased risks for assault/vandalism and driving-related harm through increased state binge drinking prevalence and a direct effect on reduced family/marital problems. Conclusions: A more stringent alcohol policy environment could reduce assault/vandalism and driving-related harm due to another drinker by lowering state binge drinking rates. Alcohol policies may not be effective in reducing family problems caused by another drinker more prevalent in low-SES states.